In Shadows and Darkness: being authentic in Céline and Hillman (“intimité des choses” and “pathologizing” ) - Novaes, Cláudio Cledson; Vrbata, Aleš (A Cor das Letras, 2017)
Aim of this paper is to demonstrate a proximity or even complementarity between James Hillman’s and Louis-Ferdinand Céline’s vision of human soul and human condition. Even though their cultural and intellectual context differed significantly and they both used very different forms of expression, they repeatedly invoked intimate dimension of human existence as permeated by somehow pathological, peripherial or dark aspects of being. Nevertheless, both of them shared deep interest in bottom-line dimension of being which they called “soul” and which they linked with death, darkness, weakness and which they associated with socially disapproved ways of being. Even though Hillman could be labeled as reformist and Céline as nihilist, for both of them modern society and its programming cut modern man off his deeper sense of meaningfulness or as Céline puts it in from “intimité des choses”. Questioning intellectual legacy of Enlightenment, both Céline and Hillman find soul of modern man as pathologized and threatened but at the same time as the very source of meaningfulness. Like that Hillman and Céline can be viewed not just as cultural critics but as actively deconstructing, questioning modern project and modern subjectivity